Sami Shamanism: Religions Variation in a Changing Ecosystem - Kasten, Erich (Culture, 1987)
Shamanism, as defined in this paper, existed among the Sami only into the 19th century. Besides its relatively early dissolution it displays certain unique features, as well as basic ideological similarities, that distinguish it from circumpolar shamanism in general. These variations are studied here as indicators of religious change in two periods of Sami history: the period of the impact of the Black Death and the period of the transition to reindeer pastoralism.